Pelatihan dan Pendampingan Mendesain Pembelajaran Berbasis Bahasa Ibu Sebagai Bahasa Transisi untuk Kemampuan Literasi Siswa Bagi Guru UPTD SDN Sobo - Lawe, Yosefina Uge; Laksana, Dek Ngurah Laba; Noge, Maria Desidaria; Ngura, Elisabeth Tantiana; Nafsia, Andi; Kaka, Pelipus Wungo (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2024)
Mother tongue is the first language understood by children.  Children who communicate daily with their mother tongue, when entering school will have difficulty understanding the learning material provided using Indonesian. Most children at an early age enter school will find it very difficult to understand Indonesian. When children are unable to understand the subject matter, the child will have difficulty in reading and writing. Therefore it is very important for teachers to do initial analysis of students' language skills to assist students in literacy. The purpose of this activity is to provide assistance to UPTD SDN Sobo teachers to design learning based on mother tongue as a transition language in improving the literacy skills of UPTD SDN Sobo students. The targets of the service activities were the principal, 12 class teachers and grade 1 and 2 students of UPTD SDN Sobo. The approach used in this program is lectures, Practice to practice. Training and mentoring will be carried out offline and online from July to October 2023. The results of this activity were the training participants, namely being able to understand the use of ibi language as a traditional language in improving literacy skills which included teaching modules, learning media and assessment instruments.